Role of SIRT1 in Hepatic Encephalopathy: In Vivo and In Vitro Studies Focusing on the NLRP3 Inflammasome. (12th October 2021) - Jiao, Fangzhou; Wang, Yao; Chen, Qian; Cao, Pan; Shi, Chunxia; Pei, Maohua; Wang, Luwen; Gong, Zuojiong
Abstract : Hepatic encephalopathy (HE) is a neuropsychiatric disorder resulting from acute or chronic liver failure. This study is aimed at investigating the therapeutic effects and mechanisms of SIRT1 in thioacetamide- (TAA-) induced rat HE models. A selective activator (CAY10602) and inhibitor (EX527) of SIRT1 were used in this study. All male rats were separated into control, TAA, CAY10602+TAA, and EX527+TAA groups. Histological damage, liver function, serum ammonia, behavioral changes, and brain oxidative stress were measured in each group. Western blotting was used to measure SIRT1, NLRP3, ASC, and IL-1 β protein expression. The results showed that CAY10602 alleviated liver injury, improved neurological decline, reduced microglial activation and brain oxidative stress, and improved the survival rates of HE rats. Moreover, CAY10602 inhibited activation of the NLRP3 inflammasome in microglia of the brain cortex in HE rats. Next, cell experiments confirmed that CAY10602 inhibited activation of the NLRP3 inflammasome in BV2 microglial cells. However, inhibition of SIRT1 by EX527 or lentivirus could enhance activation of the NLRP3 inflammasome in this process. Finally, CAY10602 reduced the neurotoxicity induced by high levels of ammonia in HT22 cells. Taken together, CAY10602 alleviates TAA-induced HE by suppressing microglial activation and the NLRP3 inflammasome and reducing the neurotoxicity of NH4 Cl in HT22 cells. A pharmacologic activator of SIRT1 may be a promising approach for the treatment of HE.